Economic Impact of Postoperative Urinary Retention in the US Hospital Setting - Weijia Wang; Arielle Marks-Anglin; Vladimir Turzhitsky; Robert J. Mark; Aurelio Otero Rosales; Nathaniel W. Bailey; Yiling Jiang; Joseph Abueg; Ira S. Hofer; Toby N. Weingarten (Journal of Health Economics and Outcomes Research, 2024)
# Background Postoperative urinary retention (POUR) is a common and distressing surgical complication that may be associated with the pharmacological reversal technique of neuromuscular blockade (NMB).